Three-Port Laparoscopic Sleeve Gastrectomy: Serial Cases Report - Gede Eka Rusdi Antara; Maria Yustina (DiscoverSys Inc., 2019)
Background: Laparoscopic sleeve gastrectomy is the procedure of choice for bariatric surgery. It is a minimally invasive procedure that giving good outcome and less complication compared to other procedures. The multiport sleeve gastrectomy technique is usually described by using 4 to 6 ports and an additional port for a liver retractor. Single-incision laparoscopic sleeve gastrectomy was reported, but not widely adopted. Â Objective: To describe a convenient and applicable modified technique of three ports laparoscopy for sleeve gastrectomy that may give better outcome and cosmetic.Cases: Four patients were diagnosed with obese class II and III. Upper GI study was performed before surgery. We performed three ports laparoscopic sleeve gastrectomy. The 15 mm port was placed in the umbilical, for the camera. The second 12 mm port was placed in the right side of the umbilical for the stapler, and the third port, 5 mm was placed in the right hypochondrium midclavicular line. During the surgery, we used endoscope as guidance during gastric stapling and also for evaluation the stapler line and the size of the stomach. The postoperative condition was uneventful, the patients have less scar and less length of stay.Conclusion: Three ports laparoscopic sleeve gastrectomy is easy to perform, convenient and applicable, consume less time and also give excellent results for the patient's recovery.Â